2012
DOI: 10.1007/s11837-012-0498-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Unexpected Ceramic Coating Phase at the Head of a Pipe on Joining and Postprocessing of a Ceramic-Lined Composite Pipe

Abstract: Produced ceramic-lined steel pipe using the self-propagating high-temperature synthesis (SHS) method has found uses in many applications. A SHScentrifugal machine was designed to produce a ceramic-lined steel pipe from ferric oxide and aluminum powder (thermite mixture) under high centrifugal acceleration. The obtained products are expected to be Al 2 O 3 ceramic in the innermost layer and a Fe layer in a region between the outer steel pipes. In the present work, specific regions of a pipe was particularly obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…This phenomenon leads to oscillatory microslipping at the components' surfaces, which actuates the existing crack nucleation and eventually leads to unanticipated structure failure. [2,3] A traditional fretting fatigue improvement strategy is coating as a surface modification method in industrial applications wherever contact parts are subjected to small amplitude relative motion as a result of vibration or cyclic loads. The effects of hard and soft coatings on fretting fatigue behavior have been studied broadly.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon leads to oscillatory microslipping at the components' surfaces, which actuates the existing crack nucleation and eventually leads to unanticipated structure failure. [2,3] A traditional fretting fatigue improvement strategy is coating as a surface modification method in industrial applications wherever contact parts are subjected to small amplitude relative motion as a result of vibration or cyclic loads. The effects of hard and soft coatings on fretting fatigue behavior have been studied broadly.…”
Section: Introductionmentioning
confidence: 99%
“…The average values of R a were used to report smoothness of the coating surface. According to the previous study of Mahmoodian et al, 8) it was found that the coating surface was smoother when R a was lower. In this study, the R a value was the lowest when the coupled additive was added at X = 3, also it agreed well with the SEM images presented in Fig.…”
Section: Characterization Resultsmentioning
confidence: 80%
“…The ceramic layer has a hardness of HV1130-HV1423, about as twice high as the steel substrate, and enhances significantly the squeezing deformation resistance as compared with an N80 steel pipe. 3. Tensile test of CLCSP shows the fracture strength of 269 MPa for the ceramic layer.…”
Section: Discussionmentioning
confidence: 99%
“…The self-propagating high-temperature synthesis in a centrifugal force field (Centrifugal SHS process) is a new technology for preparation of ceramic-lined composite steel pipes [1][2][3][4]. When thermit mixture of Fe 2 O 3 +Al is filled in a steel pipe and ignited to combust, molten products of Al 2 O 3 and Fe produced by thermit reaction can be separated in layer by virtue of their specific gravity difference under centrifugal force.…”
Section: Introductionmentioning
confidence: 99%